Integration of mitigation and adaptation in urban climate change action plans in Europe: A systematic assessment. (April 2020) - Grafakos, S.; Viero, G.; Reckien, D.; Trigg, K.; Viguie, V.; Sudmant, A.; Graves, C.; Foley, A.; Heidrich, O.; Mirailles, J.M.; Carter, J.; Chang, L.H.; et al.
Abstract: Cities are major drivers of energy consumption and greenhouse gas emissions–the sources of anthropocentric climate change, whilst also concentrating people, buildings, and infrastructures and therefore potential risk and impacts of the latter. As a consequence, planning for climate change in urban areas does not only provide the opportunity but should necessitate considering interactions between mitigation and adaptation actions. However, existing research found that only a minority of urban areas consider both mitigation and adaptation in their climate action plans, i.e. 147 Climate Change Action Plans (CCAPs) were identified among a representative sample of 885 European cities. We investigate these 147 CCAPs to understand the degree of integration of adaptation and mitigation and draw implications for the maximization of synergies and co-benefits of such a combined approach. Using the developed scoring framework to evaluate the level of integration of CCAPs, the research finds that most of the plans reveal a 'moderate' level of integration. Moderate integration characterizes a plan that identifies sources of emissions and vulnerabilities to climate change, as well as some qualitative consideration of the synergies, but one that lacks a systematic consideration of potential integration opportunities. Furthermore, the analysis reveals that one of the main gaps of the evaluation and implementation of more integrated climate change actions in cities is the insufficient quantitative evaluation of the costs and funding schemes for adaptation and mitigation action implementation. Highlights: Review and assessment of the level of integration of adaptation and mitigation in 147 EU urban climate change action plans. Development and application of the Urban Climate Change Integration Index (UCCII). Review and analysis of synergies and co-benefits of climate mitigation and adaptation actions. Mitigation objectives are still more prominent than adaptation objectives in integrated urban climate change plans. Discussion on capacity gaps and needs of local governments to understand, plan and implement integrated approaches.